2010
DOI: 10.1007/s10389-010-0376-0
|View full text |Cite
|
Sign up to set email alerts
|

Clustering behaviours among 13-year-old Portuguese adolescents

Abstract: Aim: The aims of this study were to identify clustering of behaviours in young adolescents and to analyse differences in food intake according to clusters. Subject and methods: A cross-sectional study was carried out on adolescents’ behaviours comprising 2,160 adolescents aged 13 years attending schools of Porto, Portugal. We used data of 875 girls and 737 boys with complete information for all variables considered in the cluster definition (tobacco and alcohol use, sport activities, fruit intake, daily sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…These findings are consistent with the idea that adolescents who engage in a particular unhealthy behaviour may be more prone to engage in other unhealthy behaviours 30,31 . Although it was not evaluated in this study, evidence shows that individuals with a greater tendency for thrill seeking are more likely to consume television and computer games.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with the idea that adolescents who engage in a particular unhealthy behaviour may be more prone to engage in other unhealthy behaviours 30,31 . Although it was not evaluated in this study, evidence shows that individuals with a greater tendency for thrill seeking are more likely to consume television and computer games.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, there is substantial indication that smoking and drinking tend to cluster with a number of other unhealthy behaviors which may themselves have a relevant effect on bone health [23]. One possible explanation for the associations found in the present study is indeed that these behaviors are not causal exposures but markers of other adverse influences, such as poor nutrition or sedentarism.…”
Section: Discussionmentioning
confidence: 52%
“…Regarding the indicators of socioeconomic position, in Australian adolescents the healthy pattern was associated with higher maternal education [9] and in other populations unhealthier patterns were associated with lower socioeconomic status (SES) [26,29], as in our study higher parental education level decreased the odds of being in the fast food and sweets group. Previous studies conducted in our sample of adolescents also reported unhealthier food sources of nutrients intake among adolescents from lower SES families [10], and that unhealthier lifestyles tend to aggregate [35]. In our study, dietary intake was evaluated using an FFQ.…”
Section: Discussionmentioning
confidence: 79%